2021
DOI: 10.1210/clinem/dgab304
|View full text |Cite
|
Sign up to set email alerts
|

Afirma Genomic Sequencing Classifier and Xpression Atlas Molecular Findings in Consecutive Bethesda III-VI Thyroid Nodules

Abstract: Context Broad genomic analyses among thyroid histologies have been described from relatively small cohorts. Objective Investigate the molecular findings across a large, real-world cohort of thyroid fine needle aspiration (FNA) samples. Design Retrospective analysis of RNA sequencing data files. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…In the current study, one of the most notable results is that the rate of NGAs in all 3 indeterminate categories approximated their suggested RoM according to TBS, with RAS ‐like mutations predominant in categories III and IV and BRAF V600E identified in nearly one‐half of specimens in category V. The observed rates of RAS and BRAF mutations across indeterminate TBS categories in the current study approximate those reported in previous studies 53‐55 . The observed rates of BRAF mutation across indeterminate TBS categories in the current study are particularly concordant with those in a multi‐institutional study comprising nearly 50,000 samples, although none of those institutions reported their AUS rates or III:VI ratios 56 . The observed rate of BRAF mutation specifically in TBS category V in the current study approximates a previously calculated, pooled prevalence across multiple studies, although a meta‐analysis revealed wide interstudy variation 57 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the current study, one of the most notable results is that the rate of NGAs in all 3 indeterminate categories approximated their suggested RoM according to TBS, with RAS ‐like mutations predominant in categories III and IV and BRAF V600E identified in nearly one‐half of specimens in category V. The observed rates of RAS and BRAF mutations across indeterminate TBS categories in the current study approximate those reported in previous studies 53‐55 . The observed rates of BRAF mutation across indeterminate TBS categories in the current study are particularly concordant with those in a multi‐institutional study comprising nearly 50,000 samples, although none of those institutions reported their AUS rates or III:VI ratios 56 . The observed rate of BRAF mutation specifically in TBS category V in the current study approximates a previously calculated, pooled prevalence across multiple studies, although a meta‐analysis revealed wide interstudy variation 57 .…”
Section: Discussionsupporting
confidence: 87%
“…[53][54][55] The observed rates of BRAF mutation across indeterminate TBS categories in the current study are particularly concordant with those in a multi-institutional study comprising nearly 50,000 samples, although none of those institutions reported their AUS rates or III:VI ratios. 56 The observed rate of BRAF mutation specifically in TBS category V in the current study approximates a previously calculated, pooled prevalence across multiple studies, although a meta-analysis revealed wide interstudy variation. 57 Observed rates of RAS and BRAF mutations specifically in TBS category VI also approximate those in previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, we discerned extracellular hyalinelike materials in the FNA of 1 solid variant of PTC harboring VIM-NTRK3 fusion with the correlated histomorphology. This rare fusion variant has been reported in only 1 anaplastic thyroid carcinoma 26 and <0.03% of thyroid aspiration specimens 27 without detailed morphological descriptions. To the best of our knowledge, this finding has not been reported in NTRK-rearranged PTC, and whether it could be a specific cytologic feature of this fusion type requires further validation.…”
Section: Discussionmentioning
confidence: 93%
“…10,11 A recent study of TN describes a genomic landscape with increasing mutations as FNA cytopathology progresses from Bethesda III (atypia of undetermined significance, AUS; follicular lesion of undetermined significance, FLUS; 41.5%) to Bethesda VI (malignant; 86.6%). 12 Based on this gradation, commercial molecular analytic platforms are commonly used to interrogate fine needle aspirate (FNA) samples of thyroid nodules (TN) with indeterminate cytopathology (TN-IC, Bethesda III and IV) to improve the distinction of benign form suspicious TN and inform surgical decisions. 13,14 However, the results of these and other studies have not been stratified by ethnicity.…”
Section: Introductionmentioning
confidence: 99%